AKRONIM YANG MENJADI LEKSIKON DALAM BAHASA INDONESIA - , ISTIFATUN ZAKA, Dr. Suhandano., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is a study of the acronym which becomes a lexicon in Indonesian language. The purpose of this research is to inventory the acronym which becomes a lexicon in Indonesian language, to describe the patterns forming of the acronyms which becomes a lexicon in Indonesian language, and to describe the characteristics of the acronyms which becomes a lexicon in Indonesian language. The subject of this research is acronym in Indonesian language. The object of this research is the the acronym which become a lexicon in Indonesian language. The data were obtained by the scrutinize and observation method by using note readâs technique. The method of data analysis used in this research is padan and distributional method. The padan method used some techniques, those are phonetical, orthographic, referential, and translational technique. The distributional method used some techniques. Those are basic techniques for direct elements and advanced techniques such as bottom-up, permutation, and substitution technique. The presentation of the result of the data analysis presented with the presentation of formal and informal method. The results of this research are as follows. Acronym is a morphological process in Indonesian language, although the patterns of the acronyms formation is not fixed or arbitrary. Acronyms formed by the various phonemes decision on forming components. In this research, at least, there are eighty two acronyms which are identified as lexicon in Indonesian language. Most of the lexicon of acronyms in the Indonesian language have two syllables. The phonotactics of the acronyms which becomes lexicon in Indonesian language is similar to the rules of the phonotactics Indonesian language, except in /gub/, /nud/, and /tÇg/ syllable